2011
DOI: 10.1007/s11999-010-1671-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Health-related Quality of Life after TKA in Patients who are Obese

Abstract: Background Although the health-related quality of life (HRQL) for patients who are obese seems to improve after TKA, the magnitude of improvement and the associated factors remain controversial. We previously found body mass index was not associated with changes in HRQL after TKA. Questions/purposes The purposes of this secondary analysis were to determine which patient characteristics and surgical factors were associated with worse health status after TKA in patients who are severe or morbidly obese. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Although for some outcomes (e.g. WOMAC pain score) the explained variance was small, these results are in accordance with those of other studies that used the WOMAC and SF-36 to model determinants of post-surgery outcomes [10,12,13,16]. It is important to point out that the magnitude of the associations found in this study, if taken separately, may not be clinically important, but if more than one of these characteristics is present in a patient, they are likely to have a clinically important impact [49].…”
Section: Discussionsupporting
confidence: 90%
“…Although for some outcomes (e.g. WOMAC pain score) the explained variance was small, these results are in accordance with those of other studies that used the WOMAC and SF-36 to model determinants of post-surgery outcomes [10,12,13,16]. It is important to point out that the magnitude of the associations found in this study, if taken separately, may not be clinically important, but if more than one of these characteristics is present in a patient, they are likely to have a clinically important impact [49].…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have shown that overweight and obesity have no effect on pain and mobility after TKA (Amin et al 2006, Hamoui et al 2006, Krushell and Fingeroth 2007). Other studies have shown that obese patients with a body mass index (BMI) of > 30 have worse quality of life (QoL) (Stickles et al 2001, Nunez et al 2011a), poorer mobility (Mulhall et al 2007), and less range of motion (ROM) after surgery than patients with a BMI of < 30 (Gadinsky et al 2011). They also have more pain 6 and 12 months after surgery than patients with a BMI of < 30 (Naylor et al 2011).…”
mentioning
confidence: 99%
“…Increased use of analgesics, problems with scarring (Patel and Albrizio 2008, Nunez et al 2011a), and a correlation between obesity and deep infection after TKA (Chesney et al 2008, Malinzak et al 2009) have been reported. In contrast, Suleiman et al (2012) found no difference in perioperative complication rates in patients undergoing TKA or total hip arthroplasty, based on BMI.…”
mentioning
confidence: 99%
“…An index below 1.6 corresponds to a wide knee with thicker subcutaneous cell tissue. In this same group of obese patients a relationship was found between anthropometric knee data and the functional outcomes of knee arthroplasty [41]. An infrapatellar index below 1.75 was associated with poorer functional outcomes and more pain one year after the TKA.…”
Section: Complications Associated With Knee Replacement Surgery In Obmentioning
confidence: 72%
“…2). The aim of another study by our group at the Hospital Clinic in Barcelona was to compare the health-related quality of life (HRQOL) preoperatively and at one-year follow-up in severely and morbidly obese patients undergoing total knee arthroplasty [41]. These patients had similar preoperative WOMAC scores, the only difference being in their BMI.…”
Section: Clinical and Functional Outcomes Of Total Knee Arthroplasty mentioning
confidence: 99%